2021
DOI: 10.1016/j.soard.2021.03.029
|View full text |Cite
|
Sign up to set email alerts
|

Bariatric surgery in patients with previous COVID-19 infection

Abstract: Background The process of reintroducing bariatric surgery to our communities in a COVID-19 environment was particular to each country. Furthermore, no clear recommendation was made for patients with a previous COVID-19 infection and a favorable outcome who were seeking bariatric surgery. Objectives To analyze the risks of specific complications for patients with previous COVID-19 infection who were admitted for bariatric surgery. Setting Eigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…This study shows that in patients with obesity who have survived COVID19, bariatric surgery is still safe. It is in agreement with a recently published case series including 35 European patients who underwent bariatric surgery after recovery from COVID-19 [ 17 ]. Bariatric surgery should not be considered elective in the setting of this pandemic as patients with obesity are at increased risk of mortality and it can be conducted safely both before and after infection.…”
Section: Discussionsupporting
confidence: 92%
“…This study shows that in patients with obesity who have survived COVID19, bariatric surgery is still safe. It is in agreement with a recently published case series including 35 European patients who underwent bariatric surgery after recovery from COVID-19 [ 17 ]. Bariatric surgery should not be considered elective in the setting of this pandemic as patients with obesity are at increased risk of mortality and it can be conducted safely both before and after infection.…”
Section: Discussionsupporting
confidence: 92%
“…In the current scenario of pandemic decline and relaxation of restrictive measures, bariatric surgery centers seem to gradually return to the pre-SARS-CoV-2 status, but there is still no consensus on the safety of the procedure in candidates recovered from COVID-19 [ 17 ]. Nedelcu et al aimed to provide evidence for such questioning through a multicentric cohort in which the authors described the clinical pictures of 35 individuals with severe obesity and documented previous infection by SARS-CoV-2, also analyzing their postoperative complications [ 18 ]. In comparison to the clinical evolution of patients in the preoperative group in our study, participants in that study had considerably fewer symptoms related to COVID-19 (42.9% vs 92.9%).…”
Section: Discussionmentioning
confidence: 99%
“…In the current letter ( 1 ) the authors reported two cases of patients with previous COVID-19 infection scheduled for bariatric surgery, as a reply to our initial manuscript ( 2 ). They should be commended for inciting bariatric professionals to progress in order to better address the history of COVID and future bariatric surgery, but their letter is lacking important information about these two cases, especially regarding their clinical status and preoperative pulmonary functional tests.…”
mentioning
confidence: 89%
“…They have misunderstood our conclusion and completely neglect the term “minor”. Our manuscript ( 2 ) reported 35 patients who underwent different procedures of bariatric surgery after previous COVID-19 infection. We remind the authors that the mean interval time from COVID infection to the bariatric surgery in our manuscript was of 11.3 weeks (3 – 34 weeks) and NOT 4 weeks.…”
mentioning
confidence: 99%